Uji Potensi Ekstrak Cacing Laut Eunice siciliensis Terhadap Kadar Gula Darah Tikus Rattus novergicus - Nurfahmiatunnisa Nurfahmiatunnisa; Munif S Hassan; Andi Evi Erviani (Universitas Hasanuddin, 2019)
Diabetes is a disease associated with other diseases such as heart attacks and hypertension. Research has been conducted on